The Role of Motivation, Discipline, and Work Environment in Shaping Employee Job Satisfaction: A Case Study of PDAM Bantul Regency - Muhammad Adam Dafazario (Universitas Muhammadiyah Makassar, 2025)
This study aims to examine the influence of motivation, work discipline, and work environment on the job satisfaction of employees at the Bantul Regency Regional Drinking Water Company (PDAM). The research focuses on understanding how these three factors contribute to employee satisfaction and overall workplace morale. The sample used in this study consisted of all 60 employees working at PDAM Bantul Regency. Data was collected through questionnaire distribution, ensuring comprehensive input from all participants. The collected data was then processed using the Statistical Package for the Social Sciences (SPSS) software, applying multiple linear regression analysis. The hypothesis testing was conducted at a significance level of 5% to determine the statistical relevance of each variable’s impact on job satisfaction. The results of the study indicate that motivation has a positive and significant effect on employee job satisfaction. This suggests that employees who feel motivated are more likely to experience higher job satisfaction. Similarly, work discipline also has a positive and significant effect, indicating that adherence to rules, punctuality, and consistency in work performance contribute to employees' overall job satisfaction. However, the work environment variable did not have a positive and significant effect, implying that factors such as workplace conditions, facilities, or organizational atmosphere did not significantly influence employee job satisfaction. Furthermore, the study found that motivation, work discipline, and work environment collectively have a simultaneous effect on employee job satisfaction at PDAM Bantul Regency. These findings highlight the importance of fostering motivation and discipline in improving job satisfaction, while other environmental factors may require further analysis to determine their role in employee well-being.